Types of Parental Involvement in Education, Socio-Economic Status of the Family and Students’ Academic Results - Mikhail Goshin; Tatyana Mertsalova (Voprosy obrazovaniya / Educational Studies Moscow, 2018)
The article gives an overview of the theoretical models of parental involvement in education. The peculiarities of parent involvement in Russian education are correlated with the typologies proposed by J. L. Epstein. Comparison typologies of parent involvement for different parents’ socio-economic categories was carried out. Low-income families were especially identified. It is shown that despite the fact that children from the poorest families have lower than average educational outcomes, parent involvement promotes their increase in attainment. By increasing the level of involvement that parents have, the more leveled the difference in educational results becomes. Children from the poorest families are significantly less likely to plan go to university after school. At the same time the percentage of children planning to get into higher education considerably increases when parents are involved in their education. The higher the level of parent involvement, the greater the percentage of children oriented towards getting higher education. And the higher the level of parent involvement in education, the less the gap between the low income families and average values for the sample is.